Comprehensive Analysis of Phytoestrogens Intervention to Improve Cognitive Function in Menopausal Women: A Systematic Review of Randomized Controlled Trials - Rosinta, Febi Ainnur Deavena; Deanita, Teresa Wynne; Ariyono, Muhammad Ilham Danny Wahyu; Silitonga, Thalita Kanaya (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Introduction: Dementia is marked by cognitive deficits that hinder daily functioning, with menopausal changes potentially impacting women's cognitive health and increasing dementia risk up to 70%. Studies suggest that hormone replacement therapy (HRT) can lower the risk of Alzheimer's disease in postmenopausal women, although the topic remains contentious. Phytoestrogens, which mimic estrogen, have shown promise in some trials for improving cognitive function in postmenopausal women. Consequently, the aim of this systematic review is to explore the efficacy of phytoestrogens for treating dementia and cognitive impairment in menopausal women. Material and Methods: The literature search was conducted in five databases. The outcome of interest measures the improvement of cognitive function in each included study. Different types of phytoestrogen interventions were utilized, such as isoflavone extracts with specified dosages, resveratrol, and either isolated soy protein (ISP) or soy-based products. The Cochrane Risk of Bias Tool 2 was used to assess the quality of the studies. The systematic review included a total of eight studies. Results: The review included eight studies examining phytoestrogen interventions on cognitive function in 1,464 participants aged 45 to 92. While some studies showed no significant cognitive improvements, those using resveratrol and Ginkgo biloba reported notable enhancements, particularly in memory and executive function. Given that dementia and cognitive decline are common in postmenopausal women due to lower estrogen levels, phytoestrogens may offer potential benefits. Conclusion: Phytoestrogens may improve cognitive function in menopausal women at risk of decline. However, further research is needed with more uniform populations, consistent interventions, and standardized assessments.